Evaluation of Structural and Mechanical Properties of TIG Welded Aluminium Alloy AA-5083 Subjected to Post Cryogenic Treatment - L.S, Sachin.; Mayur. S; Pavan. K.M; Chandrashekar. A; B.S. Ajaykumar (Asian Review of Mechanical Engineering, 2014)
Cryogenic treatment is a low temperature treatment process widely used in recent years to enhance the material properties without considerable sacrifice of other properties at the same time. Cryogenic engineering is a branch of material handling process which has significant commercial applications. AA-5083 is very commonly used in the manufacture of welded pressure vessels, marine, auto aircraft cryogenics, transportation equipment such as building of railroad cars, tip truck bodies, in missile components. In this study, TIG welded Aluminium alloy AA- 5083 plates were subjected to cryogenic treatment after welding and their structural and mechanical properties were evaluated. This is done in order to reveal the weld strength, hardness of welded joints by using weld current as varying parameter. After cryo processing these welded specimens were subjected to tensile test and optical microscopy (which reveals the microstructure and macrostructure of specimens). Microscopic analysis was done inorder to determine the homogeneity of the welding, the joint efficiency of welded plates and to analyze the changes in grain structure after cryogenic treatment in welded region and HAZ. Finally after observing the outcomes of the above mentioned tests higher ultimate tensile strength is obtained for higher welding current in comparison with rest of the currents. The coarse fine structure and entrapment of residual stress was improved. Hence cryogenic treatment was successful on TIG welded joints of aluminium alloy AA- 5083